Wind Resource Assessment in Europe Using Emergy - Paudel, Subodh; Santarelli, Massimo; Martin, Viktoria; Lacarrière, Bruno; Corre, Olivier Le (Journal of Environmental Accounting and Management, 2026)
In a context of increasing use of renewable sources, it is of importance to correctly evaluate the actual sustainability of their implementation. Emergy analysis is one of the possible methods useful for such an assessment. This work aims to demonstrate how the emergy approach can be used to assess the sustainability of wind energy resource in Europe. The Emergy Index of Sustainability (EIS) and the Emergy Yield Ratio (EYR) are used to analyze 90 stations of European regions for three types of wind turbines. To do so, the simplified Chou wind turbine model is used for different set of parameters as: nominal power and size of the wind turbines, and cut-in and cut-out wind speeds. Based on the calculation of the emergy indices, a mapping is proposed to identify the most appropriate locations for an implementation of wind turbines in European regions.The influence of the wind turbine type on the sustainability is also analyzed, in link with the local wind resource. Thus, it is concluded that the emergy sustainability indices are sensitive to the wind turbine design parameters (size, cut-in and cut-outwind speed).